The influence of functional warm ischemia time on DCD liver transplant recipients' outcomes. Issue 10 (29th August 2017) - Coffey, Jessica C.; Wanis, Kerollos N.; Monbaliu, Diethard; Gilbo, Nicholas; Selzner, Markus; Vachharajani, Neeta; Levstik, Mark A.; Marquez, Max; Doyle, Maria B. Majella; Pirenne, Jacques; Grant, David; Heimbach, Julie K.; et al.
Abstract: Background: Duration of functional warm ischemia (f‐WIT) is thought to have a causal effect on outcomes in controlled donation after circulatory death (DCD) liver transplantation (LT). Methods: A retrospective cohort study was conducted at five centers. Data were extracted on donor and recipient characteristics, with attention to parameters recorded during withdrawal of life support to in situ cold perfusion. F‐WIT was the time elapsed from any of the hemodynamic and oxygenation parameters to the start of in situ cold perfusion. Parameters were as follows: MAP ≤ 50 mm Hg; SBP ≤ 50 mm Hg; and SPO2 ≤ 60%. The primary endpoint was a composite of disseminated ischemic cholangiopathy (IC), primary non‐function (PNF), and early graft failure. Results: 35 patients (14%) developed one or more of the primary outcomes. On univariate analysis, older donors and longer WITs were associated with greater likelihood of complications. Of the f‐WIT variations analyzed, only f‐WIT with SpO2 ≤ 60% was longer among patients with complications. On multivariate analysis, only donor age was a significant predictor of complications. Conclusion: This study demonstrates that, of the f‐WITs, f‐WIT with SpO2 ≤ 60% is most predictive of post‐DCD complications. However, results suggest that there may be an alternate etiology for poor outcomes, and that donor age plays a key role.